Heat Shock Protein 20 Gene Superfamilies in Red Algae: Evolutionary and Functional Diversities - Gao, Tian; Mo, Zhaolan; Tang, Lei; Yu, Xinzi; Du, Guoying; Mao, Yunxiang (Frontiers in Plant Science, 2022)
Heat shock protein 20 (Hsp20) genes play important roles in plant growth, development, and responses to environmental stresses. However, the Hsp20 gene family has not yet been systematically investigated, and its role in red algae (Rhodophyta) remains poorly understood. Here, we characterized the Hsp20 gene families in eight red algae by studying gene structure, conserved motifs, phylogenetic relationships, chromosome location, gene duplication, cis-regulatory elements, and expression profiles. In this study, 49 Hsp20 genes were identified using bioinformatics methods and classified into 13 subfamilies based on phylogenetic relationships. Phylogenetic analysis revealed that Hsp20 genes might have a polyphyletic origin and a complex evolutionary pattern. The gene structure analysis showed that most Hsp20 genes possessed no introns, and all Hsp20 genes contained a conserved α-crystalline domain in the C-terminal region. Hsp20 genes belonging to the same subfamily were revealed to share similar motifs via conserved motif analysis. Gene duplication analysis demonstrated that tandem duplication and segmental duplication events occurred in these gene families. Additionally, these gene families in the red algae might have experienced strong purifying selection pressure in the process of evolution, and Hsp20 genes in Pyropia yezoensis, Pyropia haitanensis, and Porphyra umbilicalis were highly conserved evolutionally. The cis-elements of phytohormone-, light-, and stress-responsive, and development-related were identified in the red algal Hsp20 gene promoter sequences. Finally, using Py. yezoensis as a representative of red algae, the Hsp20 gene expression profile was explored. Based on RNA-seq data, PyHsp20 genes were involved in Py. yezoensis responses against abiotic and biotic stresses and exhibited diverse expression patterns. Moreover, PyHsp20 genes were involved in Py. yezoensis growth and development and revealed spatial and temporal expression patterns. These results provide comprehensive and valuable information on the Hsp20 gene families in red algae and lay a foundation for their functional characterization. In addition, our study provides new insights into the evolution of red algal Hsp20 gene families and will help understand the adaptability of red algae to diverse environments.